(untitled) (Research, Society and Development, 2021)
Root fractures are defined as those that involve cement, dentin and pulp, comprising from 1,2 to 7% of injuries in permanent dentition. Usually affects the maxillary anterior region, and generally heals spontaneously, depeding on the vitality of the pulp. Diagnosis is made by clinical findings, sensitivity tests and radiographic examination. Futhermore, cone-beam computed tomography (CBCT) has been used for diagnosis and prognosis, due to the reproduction of three-dimensional images, the location and the path of the fracture line can be accurately visualized. This study reports a case of dental trauma caused by fall from own height. The patient suffered horizontal root fracture in maxillary left central incisor, wich was confirmed from radiographic examination, positioned at the end of the middle third. As immediate treatment, it was performed the repositioning and spliting. To confirm the exact location of the fracture and if healing occurred, CT images of the were performed 30 days after the trauma and the fracture with an oblique path healed by calcified tissue could be visualized. In this way, it was decided to follow-up the horizontal radicular fracture with the control time of:15 days, 30 days, 60 days, 2 years and 5 years. It alllowed the tooh to be preserved in the arch, with normal function.